Pengaruh Senam Aerobic Di Pagi Hari Dan Malam Hari Terhadap Kadar Vo2 Max - DINATA, Agung Rangga; , Wahyuni, SSt.FT.M.Kes; , Umi Budi Rahayu, SSt. Ft. SPd. M. Kes (2015)
VO2max levels associated with a person's ability to work the muscles . If someone does work, the more severe the work done, the higher oxygen consumption. The number of muscles involved in the muscle's ability to utilize oxygen supplied influenced by muscle mass. Aerobic exercise was exercise that uses the energy from the combustion with oxygen, and requires oxygen without incurring oxygen debt unpaid. Effects of aerobic exercise include cardio respiratory fitness, because the sport was able to increase the uptake of oxygen , increasing the capacity of the blood to carry oxygen and pulse rate will be lower at rest and activity. Sports in the morning was a prevalent form of exercise than exercise at night . Some experts said that there were many shortcomings in exercising at night . Weaknesses associated with the biological clock which at night was a time - time start resting human body . This study aims to determine differences in VO2max levels of aerobic exercise in the morning and evening. The study design was observational cross-sectional design. The amount of sample was 64 people, divided into 32 groups and 32 in the morning aerobic night. The samples using purposive sampling with the terms of inclusion and exclusion. Data were analyzed using Mann Whitney test. The data obtained in the study were not normally distributed. The results of the analysis of Mann Whitney Test VO2 Max levels obtained Zobs value of - 2.814 with a p-value of 0.005. P-value < 0.05 then the decision was a test of H0 was rejected, meaning that there were significant differences between the levels of VO2 Max aerobic exercise mornings and evenings. Furthermore, the average value of VO2 Max group was higher in the morning than the evening group (51.04 > 46.91). With the results of the analysis, it was concluded that the morning aerobic exercise has the effect of increased levels of VO2Max was better than aerobic exercise the evening.